Determinants of Skin Disease Complaints in Informal Shellfish Workers: A Study from Cinta Damai Village - Nabila, Nazua; Wahyudi; Hasibuan, Rapotan (The Indonesian Institute of Science and Technology Research, 2025)
Clam processing workers often receive limited attention in occupational health discussions, particularly concerning skin disease complaints, which are strongly suspected of being associated with inadequate personal hygiene practices. This study aimed to examine the effect of personal hygiene on skin disease complaints among clam processing workers. Quantitative research design was employed using a cross-sectional approach. The study involved 67 respondents, selected through total sampling. Data was analyzed using univariate, bivariate, and multivariate methods, with logistic regression applied for multivariate analysis. The results indicated that, after controlling for other variables, skin hygiene as well as nail and hand hygiene were significant factors influencing skin disease complaints. Although hair hygiene was not statistically significant, the relationship trend suggested that individuals with poor hair hygiene had a 7.9 times higher likelihood of experiencing skin-related complaints. Among all variables, skin hygiene emerged as the most influential factor, with an Exp(B) value of 34.869, suggesting that workers with poor skin hygiene were 34.869 times more likely to report skin diseases compared to those with good skin hygiene. The model explained 79.7% of the variance in skin disease complaints, indicating a strong influence of personal hygiene. These findings underscore the critical role of personal hygiene in preventing occupational skin diseases among clam processing workers.